Intermolecular and Intramolecular Interactions Regulate Catalytic Activity of Myotonic Dystrophy Kinase-Related Cdc42-Binding Kinase α - Tan, Ivan (American Society for Microbiology, 2001)
Myotonic dystrophy kinase-related Cdc42-binding kinase (MRCK) is a Cdc42-binding serine/threonine kinase with multiple functional domains. We had previously shown MRCKα to be implicated in Cdc42-mediated peripheral actin formation and neurite outgrowth in HeLa and PC12 cells, respectively. Here we demonstrate that native MRCK exists in high-molecular-weight complexes. We further show that the three independent coiled-coil (CC) domains and the N-terminal region preceding the kinase domain are responsible for intermolecular interactions leading to MRCKα multimerization. N terminus-mediated dimerization and consequent transautophosphorylation are critical processes regulating MRCKα catalytic activities. A region containing the two distal CC domains (CC2 and CC3; residues 658 to 930) was found to interact intramolecularly with the kinase domain and negatively regulates its activity. Its deletion also resulted in an active kinase, confirming a negative autoregulatory role. We provide evidence that the N terminus-mediated dimerization and activation of MRCK and the negative autoregulatory kinase–distal CC interaction are two mutually exclusive events that tightly regulate the catalytic state of the kinase. Disruption of this interaction by a mutant kinase domain resulted in increased kinase activity. MRCK kinase activity was also elevated when cells were treated with phorbol ester, which can interact directly with a cysteine-rich domain next to the distal CC domain. We therefore suggest that binding of phorbol ester to MRCK releases its autoinhibition, allowing N-terminal dimerization and subsequent kinase activation.